A Starch-Milk Paste Enables the Incorporation of Ripened Cheese in Novel Fresh Cheese - Elpiniki Palyvou-Gianna; Tatiana Paula Vilela; Ana Maria Gomes; João Paulo Ferreira (Food Technology and Biotechnology, 2021)
Research background. Fresh cheese varieties represent an important share of the whole cheese market. Although with great variability in terms of composition and method of preparation, fresh cheese varieties are bland in flavour and their production originates whey drainage. On the other hand, the cheese market is also responsible for a significant amount of food waste. These motivated the development of a novel fresh cheese incorporating ripened cheese, which can then represent a valorisation of ripened cheese surpluses. Experimental approach. A variable amount of ripened cheese was dispersed in a paste of gelatinized starch (normal corn or waxy rice) in milk, producing melted cheese bases. These cheese bases were diluted with milk, sometimes enriched with skimmed milk powder, and then renneted. Macronutrient content and physical properties of the resultant fresh cheese were characterized. Sensory analyses of samples incorporating mature Cheddar, goat’s or ewe’s cheese were carried out. Results and conclusions. Gel formation of the initial mixture was hindered above 8% (m/m) incorporation of ripened cheese, which could be overcome by the addition of skimmed milk powder. These observations are corroborated by the hardness values from texture analysis tests. Evaluation of syneresis of different samples enabled to conclude that the addition of 2% (m/m) starch and 2.8% (m/m) skimmed milk powder contributes to reduction of its magnitude by half. Sensory analysis with a consumer panel indicated a preference for a more consistent texture of the fresh cheese, and for the Cheddar flavour. Novelty and scientific contribution. A novel fresh cheese variety incorporating dispersed ripened cheese was prepared. The proposed method is versatile and quite straightforward and does not use polyphosphate salts or originate whey wastage. The fresh cheese physical and sensorial properties can be manipulated by the amounts and types of added starch, ripened cheese and skimmed milk powder; such tailoring of fresh cheese properties widens product portfolio capacity for a larger number of consumer groups. The added ripened cheese can come from non-sellable pieces and unsold stocks from the retail sector, contributing to a reduction of food waste.